Tadlīs al-Taswiyah and the Regulatory Standards for Accepting the 'An‘anah of Narrators Described by it - Dr. Khalid Atiya Saad (Journal of Scientific and Human Dimensions, 2026)
This research provides a specialized Hadith study into one of the most intricate and subtle aspects of hidden defects (‘Ilal) in chains of transmission (Isnad): Tadlīs al-Taswiyah (Settlement Deception). It explores its conceptual reality and its critical manifestations. The study highlights the core research problem: the discrepancy between theoretical framing which often deems the explicit mention of audition (Sama‘) by the Mudallis from their immediate teacher and their teacher’s teacher as sufficient and the applied methodology of Hadith critics and contemporary scholars. These experts exercise greater caution regarding the ‘An‘anah (narrating using the term "from") of those characterized by this practice, requiring explicit confirmation of Sama‘ across all layers of the Isnad. This investigation is grounded in their scholarly dictates and practical applications. The research concludes that while the theoretical framework holds weight, the applied methodology is more prudent for mitigating the risks of Tadlīs and ensuring the integrity of narrations. Furthermore, the study establishes governing criteria and circumstantial evidence (Qara’in) to regulate this issue, thereby enriching Hadith principles and assisting researchers in the practical study of narrations involving Tadlīs al-Taswiyah.
Keywords: Tadlīs; Tadlīs al-Taswiyah; ‘An‘anah; Samā‘ (Audition)